Localization of Herpes Simplex Virus Type 1 UL37 in the Golgi Complex Requires UL36 but Not Capsid Structures - Desai, Prashant (American Society for Microbiology (ASM), 2008)
The herpes simplex virus type 1 (HSV-1) UL37 gene encodes a 120-kDa polypeptide which resides in the tegument structure of the virion and is important for morphogenesis. The goal of this study was to use green fluorescent protein (GFP) to follow the fate of UL37 within cells during the normal course of virus replication. GFP was inserted in frame at the C terminus of UL37 to generate a fluorescent-protein-tagged UL37 polypeptide. A virus designated K37eGFP, which replicated normally on Vero cells, was isolated and was shown to express the fusion polypeptide. When cells infected with this virus were examined by confocal microscopy, the fluorescence was observed to be predominantly cytoplasmic. As the infection progressed, fluorescence began to accumulate in a juxtanuclear structure. Mannosidase II and giantin were observed to colocalize with UL37eGFP at these structures, as judged by immunofluorescence assays. Therefore, UL37 traffics to the Golgi complex during infection. A VP26mRFP marker (red fluorescent protein fused to VP26) was recombined into K37eGFP, and when cells infected with this “dual-color” virus were examined, colocalization of the red (capsid) and green (UL37) fluorescence in the Golgi structure was observed. Null mutations in VP5 (ΔVP5), which abolished capsid assembly, and in UL36 (Δ36) were recombined into the K37eGFP virus genome. In cells infected with K37eGFP/ΔVP5, localization of UL37eGFP to the Golgi complex was similar to that for the parental virus (K37eGFP), indicating that trafficking of UL37eGFP to the Golgi complex did not require capsid structures. Confocal analysis of cells infected with K37eGFP/Δ36 showed that, in the absence of UL36, accumulation of UL37eGFP at the Golgi complex was not evident. This indicates an interaction between these two proteins that is important for localization of UL37 in the Golgi complex and thus possibly for cytoplasmic envelopment of the capsid. This is the first demonstration of a functional role for UL36:UL37 interaction in HSV-1-infected cells.